Lumefantrine ameliorates DSS-induced colitis by targeting FLI-1 to suppress NF-κB signaling - Yang, Ji; Guo, Peng; Luo, Hongtao; Tang, Xin; Liu, Wei; Ren, Xiaolin (Frontiers in Pharmacology, 2025)
BackgroundCurrent therapeutic options for inflammatory bowel disease (IBD) remain suboptimal due to limited efficacy, significant side effects, and high relapse rates, necessitating novel treatment strategies. Lumefantrine, a clinically established antimalarial drug, emerges as a compelling repurposing candidate based on its putative anti-inflammatory activity, though its efficacy and mechanism in IBD remain unexplored.MethodsA murine IBD model was induced by 3% dextran sulfate sodium (DSS). Mice received oral Lumefantrine (20 mg/kg/day) for 7 days. Disease progression was monitored via disease activity index (DAI) scoring and histological analysis. Serum cytokines (IL-1β, IL-6, TNF-α) and colonic inflammatory mediators (Cox-2, iNos) were quantified by ELISA and qPCR. Tight junction proteins (Claudin-1, ZO-1) were assessed by immunohistochemistry and Western blot. Molecular targets were identified through computational docking and pull-down assays. Additionally, NF-κB signaling modulation was assessed in lipopolysaccharide (LPS)-stimulated intestinal epithelial cells (IEC-6 and NCM460) via Western blot analysis.ResultsOral administration of Lumefantrine significantly attenuated disease activity index (DAI) scores and restored intestinal barrier integrity through upregulation of epithelial tight junction proteins Claudin-1 and ZO-1. Treated mice exhibited reduced serum levels of IL-1β, IL-6 and TNF-α, along with decreased colonic expression of inflammatory mediators cyclooxygenase-2 (Cox-2) and inducible nitric oxide synthase (iNos). Computational and experimental approaches identified FLI-1 a transcription factor upregulated in IBD colon tissues as Lumefantrine’s direct binding target. This interaction mediated suppression of NF-κB signaling, specifically downregulating phosphorylation of IκBα and p65 in LPS-stimulated intestinal epithelial cells.ConclusionLumefantrine ameliorates experimental colitis through FLI-1-dependent inhibition of the NF-κB pathway, demonstrating high repurposing potential as an IBD therapeutic.